Bladder carcinoma: understanding advanced and metastatic disease with potential molecular therapeutic targets. Issue 6 (December 2005) - Ahmed, Hashim Uddin; Arya, Manit; Patel, Hitendra RH
This article is an expert review of bladder cancer genetics focusing on genetic changes and their significance in the pathogenesis and progression of bladder transitional cell carcinoma, in particular, muscle-invasive disease. Alongside the relevant genetic markers and their products, new therapeutic targets and agents that are being developed are presented.